What needs to change in Babati for smallholder farmers to sustainably intensify? Lessons from 10 years of community action research: Evidence from Babati - Kihara, Job Maguta; Kinyua, Michael; Massam, Jonus; Pallagjo, Rose; Songoyani, Inot; Kyekaka, Jetrida (2022)
This brief presents existing opportunities to achieve increased crop production, diet diversification and increased incomes by smallholder farming households in Babati, Tanzania. It is based on a series of experimental research conducted under Africa RISING since 2012 including nutrient response trials, testing of different intercropping options, and socio-economic assessments. The work was implemented in several villages in Tanzania’s Babati District including Long, Seloto, Sabilo, Gallapo, Qash, Ayamango, Riroda, Hallu, Duru and Endanachan. Maize, beans, pigeonpea and potatoes are the major crops cultivated for both subsistence and commercial purposes by smallholders within Babati.